Aqidah Deviations in the Millennial Era - Sori Monang; Bambang Saputra; Anwar Fauzi (Budapest International Research and Critics University, 2021)
In religious life that occurs in this millennial era, there are many misunderstandings regarding the issue of aqidah and other faith issues. Thoughts, ideologies, and activities that are contrary to aqidah and sharia, of course, cannot just develop in the community because they will cause people's unrest and cause people to become victims of misguidance. Without the right aqidah one will fall prey to suspicion or accusations and also doubts so that gradually it will hinder people from the right view. People's behavior like this will inevitably lead to deviations in the implementation of religious teachings. Therefore, serious efforts must be made to stop and awaken them to return to the right path.